Analisis Penerimaan Implementasi Smart Classroom Berdasarkan Perspektif Pengguna di Fakultas Pertanian Universitas Brawijaya dengan Menggunakan Technology Acceptance Model (TAM) Termodifikasi - Erwina Nur Amalina; Aditya Rachmadi; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In its implementation, Smart Classroom in the Faculty of Agriculture, Universitas Brawijaya is still relatively new and there are still complaints from students or lecturers as users. Evaluation needs to be done so that it gets recommendations for improvements to improve Smart Classroom acceptance. This study uses a modified Technology Acceptance Model (TAM) using four variables, namely perceived ease of use, perceived usefulness, behavior intention to use, actual system to use. These variables were examined to describe user acceptance of Smart Classroom with descriptive statistical analysis. Data retrieval is done using offline questionnaire instruments and interviews. The population in this study were Agriculture Faculty students who used Smart Classroom with a sample of 32. The results showed that the variables perceived ease of use (76,70%), perceived usefulness (77,76%), behavioral intention to use (81,30%), the actual system to use (80,80%) belongs to the high category. From the results of the study, recommendations for improvements were made to improve Smart Classroom acceptance.